PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WEB ARTICULATE STORYLINE PADA PEMBELAJARAN IPA DI KELAS V SEKOLAH DASAR - Arum Donna Safira; Iva Sarifah; Tunjungsari Sekaringtyas (Prima Magistra: Jurnal Ilmiah Kependidikan, 2021)
Based on the needs analysis, it is necessary to develop interactive learning media. This research and development aims to produce products in the form of articulate storyline web-based interactive learning media for natural science learning and to find out the validation of web articulated storyline-based interactive learning media for science learning in grade V Elementary School. The samples in this study were 9 grade 5 elementary school students in the neighborhood around the researcher's house. The development model used in this study is the ADDIE development model (analyze, design, development, implementation and evaluation). Data collection techniques were carried out by interviews and questionnaires. Data analysis using Miles and Huberman model analysis. The trial results of developing interactive learning media based on web articulate storylines with media experts, materials experts, and learning design experts obtained an average value of 95% with the criteria "very feasible". The results of the one to one trial get an average score of 98.8% and the results of the small group trial get an average value of 99.4%. Referring to the results of data analysis of the Miles and Huberman’s model, the articulate storyline web-based interactive learning media is very suitable for use by fifth grade students in science learning in elementary schools.